Gentleman Spies : Intelligence Agents in the British Empire and Beyond - Fisher, John (Stroud, England Sutton Publishing Limited, 2002)
Examines the world of the secret service in the last days of the British Empire. The author's research in the Public Records Office shows what the secret service was up to in the years before and directly after World War I, disclosing facts about those recruited to work as undercover agents.
Include Illustrations, Figures, Bibliography and Index.
Keywords: Spies -- Secret service -- Great Britain -- Secret service -- Great Britain -- History -- 20th century